Three challenges that the COVID-19 pandemic represents for psychiatry - Kesner, Ladislav; Horáček, Jiří (The British journal of psychiatry, 2020)
The evolving COVID-19 pandemic and its likely consequences add to the already substantial psychosocial burden caused by global problems, existential threats and heightened uncertainty, which are increasingly confronting communities worldwide. Here we briefly outline three challenges for clinical psychiatry and research, related to coping with the social epidemiology of negative moods, stress and socially mediated traumatic experiences brought on by these adverse developments.
Keywords: virová pneumonie; podrážděnost; Pandemics; negative mood; psychický stres; koronavirové infekce; adaptace psychologická; Mental Health; psychologie; COVID-19; media; Stress, Psychological; Coronavirus Infections; nejistota; uncertainty; mental health; duševní zdraví; sociální média; Adaptation, Psychological; Humans; celosvětové zdraví; Social Media; Global Health; Irritable Mood; Uncertainty; pandemie; Pneumonia, Viral; lidé; Psychology